Initial application of bio-logging techniques on captive Milky Storks (Mycteria cinerea) in Malaysia. - Ismail, Ahmad; Rahman, Faid; Miyazaki, N.; Naito, Y. (International Society for Tropical Ecology, 2012)
The use of remote sensing equipment on animals (i.e. bio-logging) is increasingly being used to understand numerous variables about their life at very fine temporal scales. While bio.logging has been used extensively in seabirds, it has only been used minimally in freshwater birds. Given the relatively new development of this technology, we conducted a preliminary study to understand the behavior of captive Milky Storks (Mycteria cinerea) using digital data loggers between 2009 and 2010 in Zoo Negara, Malaysia. Data loggers were attached to seven individuals to record axes of acceleration of movements and temperature as part of a study to develop the appropriate techniques for data logger use with this species. The birds' activities were also recorded by direct observations to assist in interpreting the output from the loggers. Detailed routine activities along with the temperature of the surrounding environment were obtained in this study; This includes normal activity such as flying, preening, roosting and aggressive displays such as the clattering threat and the anxiety stretch. With some adjustment, the study can be repeated in the wild to study the birds' detailed behavior and ecological information on their surroundings.